Artificial intelligence, algorithms and antitrust. Issue 4 (December 2019) - Rab, Suzanne
Abstract : The field of artificial intelligence or 'AI' has been reshaping virtually every industry built on the idea that machines could be used to simulate human intelligence through so-called 'machine learning'. Antitrust interest in this topic has been generated among regulators, policy-makers, academics and business in the EU and internationally. This article explores the extent to which AI may raise competition or other concerns for consumer welfare and whether existing legal and policy instruments are appropriate to deal with the emerging opportunities and challenges.